Hypoglycemic Activity and the Potential Mechanism of the Flavonoid Rich Extract from Sophora tonkinensis Gagnep. in KK-Ay Mice - Huang, Mi; Deng, Shihao; Han, Qianqian; Zhao, Ping; Zhou, Qi; Zheng, Sijian; Ma, Xinhua; Xu, Chan; Yang, Jing; Yang, Xinzhou (Frontiers in Pharmacology, 2016)
This study investigated the active principles, hypoglycemic activity and potential mechanisms of the flavonoid rich extract from Sophora tonkinensis Gagnep. (SS-EtOAc) in KK-Ay diabetic mice. An off-line semipreparative LC-NMR and LC-UV-ESIMS protocol was performed to determine 13 flavonoids from SS-EtOAc. SS-EtOAc administrated orally to the KK-Ay mice significantly increased their sensibility to insulin, reduced fasting blood-glucose levels and blood lipid indexes such as triglyceride and cholesterol. Moreover, SS-EtOAc exhibited a strong effect of stimulation on GLUT4 translocation by 2.7 fold in L6 cells. However, the selective AMP-activated protein kinase (AMPK) inhibitor Compound C can completely inhibit the activation of the AMPK pathway and prevent the GLUT4 translocation caused by SS-EtOAc. In vivo, phosphorylation of the AMPK expression in the liver and skeletal muscle was measured. The results showed phosphorylation of the AMPK had been improved and GLUT4 expression had been also enhanced. In this paper we conclude that, SS-EtOAc seems to have potential beneficial effects on the treatment of type 2 diabetes mellitus (T2DM) with the probable mechanism of stimulating GLUT4 translocation modulated by the AMPK pathway.